2005
DOI: 10.1007/s11244-005-7863-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Copper on Single Crystalline ZnO: Surface Study of a Model Catalyst

Abstract: Copper, vapor-deposited on the polar, Zn-terminated ZnO(0001) surface is investigated in view of its suitability as model system for the technologically important Cu/ZnO catalyst. The structure and electronic properties of Cu clusters on ZnO(0001)-Zn have been studied with scanning tunneling microscopy (STM), low energy electron diffraction (LEED), ultraviolet photoelectron spectroscopy (UPS), and low-energy He + ion scattering (LEIS). At room temperature copper grows as two-dimensional (2D) clusters only at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 69 publications
11
78
1
Order By: Relevance
“…Nucleation and growth of Cu has been explored on the polar ZnO (0001) surface, revealing the formation of 3D particles on the Zn-terminated, but 2D-wetting growth on the O-terminated surface due to the larger Cu-O interaction in the latter case. 361,362 On the non-polar ZnO(10-10), mainly the adsorption of hydrogen 35,363 and water 286,311,364 has been studied. Interestingly, binding of a single H-atom per surface unit cell gives rise to a metallization of the initially semiconducting oxide, as demonstrated by STM conductance spectroscopy and HREELS (Fig.…”
Section: Fig 46mentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleation and growth of Cu has been explored on the polar ZnO (0001) surface, revealing the formation of 3D particles on the Zn-terminated, but 2D-wetting growth on the O-terminated surface due to the larger Cu-O interaction in the latter case. 361,362 On the non-polar ZnO(10-10), mainly the adsorption of hydrogen 35,363 and water 286,311,364 has been studied. Interestingly, binding of a single H-atom per surface unit cell gives rise to a metallization of the initially semiconducting oxide, as demonstrated by STM conductance spectroscopy and HREELS (Fig.…”
Section: Fig 46mentioning
confidence: 99%
“…Unfortunately, the number of such experiments performed with the STM is surprisingly small. Most of them deal with polar ZnO(0001) surfaces, 361,363 or explore the hydroxylation of thin oxide films with polar character, for instance of Cr 2 O 3 /Cr(110) 402 or more recently of FeO/Pt(111). 303 For the latter system, also experiments on other atomic and molecular adsorbates have been performed with low-temperature STM, which shall be presented in the following.…”
Section: Adsorption On Polar Oxide Filmsmentioning
confidence: 99%
“…Dulub et al [11] found 3D-cluster growth already for very low coverages >0.01 ML. The Cu-clusters are aligned with respect to the ZnO-substrate and the LEED pattern shows (1 1 1)-orientation with the lattice constant of bulk Cu(1 1 1) (21% smaller relative to the ZnO lattice) [4].…”
Section: Introductionmentioning
confidence: 97%
“…In catalysis this system is very important because it plays a significant role in the technologically important methanol synthesis from CO/CO 2 /H 2 reactants and hydrogen production from methanol by the reverse water gas-shift reaction [4][5][6][7]. The oxide (ZnO) is an essential part of the catalyst and although many groups work on catalyst characterisation, the mechanisms that make this combination of material such a successful catalyst are still unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…Typical ZnO materials exhibit a würtzite structure with the polar planes corresponding to the basal planes of the hexagonal würtzite unit cell [36][37][38]. The würtzite configuration has preferential exposure of non-polar facets (lower polarity ratio).…”
Section: Catalytic Activity Of Cuo/zno Samples In the Conventional Rementioning
confidence: 99%